Fish Associations among Un‐notched, Notched and L‐head Dikes in the Middle Mississippi River. (12th March 2015) - Braun, Andrew P.; Sobotka, Molly J.; Phelps, Quinton E.
Abstract: Wing dikes and other anthropogenic modifications have heavily altered riverine ecosystems. Recent efforts to reach a compromise between the needs of the river transportation industry and natural resource conservation include dike modification. Dike notching permits water flow through the landward portion of the dike and has been purported to provide suitable habitat for fish and other river biota while maintaining the navigation channel. L‐head dikes are flow‐control structures that create calm backwater‐like habitats downstream. However, few researchers have examined the actual effects of dike notching on water quality or fish communities. We compared standardized catch per unit effort and overall community structure for 50 fish species among un‐notched dikes, notched dikes and L‐head dikes in the Middle Mississippi River, sampled as part of the US Geological Survey's Long‐Term Resource Monitoring Program. There were no differences in standardized catch per unit effort for 64% of the fishes examined. Five species known to be associated with lotic habitats were most abundant near L‐head dikes. Seven species were more abundant at un‐notched dikes than notched dikes, while six species were more abundant at notched dikes than un‐notched dikes. Non‐metric multidimensional scaling suggested differences in overall fish community structure between un‐notched and other dike types. Detailed physical habitat studies should be conducted to better understand the effects of dike modification. Copyright © 2015 John Wiley & Sons, Ltd.